Lymphogranuloma venereum and HIV infection: misdiagnosed as Crohn's disease. (26th November 2010) - Patel, Sheel; Hay, Phillip
Abstract : The report describes a young Caucasian homosexual man who presented with a 4-month history of bloody diarrhoea and weight loss. Over the next 4 months he was investigated for inflammatory bowel disease and subsequently started on mesalazine and prednisolone as an outpatient. Within a month of starting treatment his symptoms worsened, leading to his self-referral to the genitourinary medicine clinic. The patient was subsequently diagnosed with advanced HIV infection and lymphogranuloma venereum infection. The patient was treated with doxycycline for 3 weeks and started on antiretrovirals. One month later the patient is symptom free with a recovering immune system.